2005
DOI: 10.1128/aac.49.2.798-800.2005
|View full text |Cite
|
Sign up to set email alerts
|

Test Characteristics of Perirectal and Rectal Swab Compared to Stool Sample for Detection of Fluoroquinolone-Resistant Escherichia coli in the Gastrointestinal Tract

Abstract: Among 63 patients enrolled in a prospective cohort study of gut colonization with fluoroquinolone-resistant Escherichia coli, the sensitivity of perirectal swab compared to stool sample was 90% (95% confidence interval [CI], 70 to 99%) and the specificity was 100% (95% CI, 91 to 100%). For rectal swab, the sensitivity was 90% (95% CI, 68 to 99%) and the specificity was 100% (95% CI, 91 to 100%).Resistance to many antimicrobial drugs has increased significantly among gram-negative bacilli (GNB) in recent years … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
60
0

Year Published

2008
2008
2020
2020

Publication Types

Select...
8
2

Relationship

2
8

Authors

Journals

citations
Cited by 71 publications
(61 citation statements)
references
References 12 publications
1
60
0
Order By: Relevance
“…Because perirectal swabs are less invasive and may be more acceptable to patients, our data provide support for the use of perirectal swabs as the preferred method for the detection of carriers. Our findings are consistent with previous studies demonstrating that perirectal swabs are equivalent to rectal swabs for the detection of rectal carriers of vancomycin-resistant enterococci and fluoroquinolone-resistant Escherichia coli (6,7).…”
supporting
confidence: 83%
“…Because perirectal swabs are less invasive and may be more acceptable to patients, our data provide support for the use of perirectal swabs as the preferred method for the detection of carriers. Our findings are consistent with previous studies demonstrating that perirectal swabs are equivalent to rectal swabs for the detection of rectal carriers of vancomycin-resistant enterococci and fluoroquinolone-resistant Escherichia coli (6,7).…”
supporting
confidence: 83%
“…The intestine/rectal flora is a likely source of the resistant organisms being introduced into the bloodstream at the time of the biopsy and is the logical site to isolate bacteria which may be a future offending organism. In this study, we used rectal swabs, since they have been shown by others to have comparable sensitivity and specificity to the gold standard, fecal specimens, for the detection of fluoroquinolone-resistant E. coli from the intestine (8). Many groups have monitored the prevalence of fluoroquinoloneresistant organisms by using rectal or fecal specimens (2,7,14).…”
mentioning
confidence: 99%
“…For this reason faecal samples may perform better than rectal swabs 9 , although the latter is more practical. Using more than one screening specimen or specimen type may increase sensitivity 6 , but again for practical purposes one specimen is usual.…”
mentioning
confidence: 99%